Insights Into the Coinfections of Human Immunodeficiency Virus-Hepatitis B Virus, Human Immunodeficiency Virus-Hepatitis C Virus, and Hepatitis B Virus-Hepatitis C Virus: Prevalence, Risk Factors, Pathogenesis, Diagnosis, and Treatment - Shahriar, Sagarika; Araf, Yusha; Ahmad, Rasel; Kattel, Pravakar; Sah, Ganga Sagar; Rahaman, Tanjim Ishraq; Sadiea, Rahila Zannat; Sultana, Shahnaj; Islam, Md. Sayeedul; Zheng, Chunfu; Hossain, Md. Golzar (Frontiers in Microbiology, 2022)
Human immunodeficiency virus, hepatitis B virus, and hepatitis C virus are three blood-borne viruses that can cause major global health issues by increasing severe morbidity. There is a high risk of coinfection with these viruses in individuals because of their same transmission routes through blood using shared needles, syringes, other injection equipment, sexual transmission, or even vertical transmission. Coinfection can cause various liver-related illnesses, non-hepatic organ dysfunction, followed by death compared to any of these single infections. The treatment of coinfected patients is complicated due to the side effects of antiviral medication, resulting in drug resistance, hepatotoxicity, and a lack of required responses. On the other hand, coinfected individuals must be treated with multiple drugs simultaneously, such as for HIV either along with HBV or HCV and HBV and HCV. Therefore, diagnosing, treating, and controlling dual infections with HIV, HBV, or HCV is complicated and needs further investigation. This review focuses on the current prevalence, risk factors, and pathogenesis of dual infections with HIV, HBV, and HCV. We also briefly overviewed the diagnosis and treatment of coinfections of these three blood-borne viruses.